FAKTOR - FAKTOR YANG MEMENGARUHI REPURCHASE INTENTION PADA PENGGUNA LAZADA DIDKI JAKARTA - ANDINI, RISKI; AGUNG TRIANDEWO, MARIS (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This study aims to test and analyze whether Perceived Enjoyment, Perceived Ease of Use, Satisfaction, and Trust are factors that influence Repurchase Intention. In addition, this study also examines and analyzes the effect of Perceived Enjoyment, Perceived Ease of Use, Satisfaction, Trust on Repurchase Intention on Lazada users in DKI Jakarta. The research design used is descriptive and causality research using a Likert scale and using five measurement points. The sampling technique that will be used in this research is to use a purposive sampling method with primary and secondary data. The sample used was 110 Lazada user respondents, the data was processed using the Multiple Linear Regression method with the SPSS program as a test tool. The results obtained in this study show the influence of Perceived Enjoyment, Satisfaction and Trust on Repurchase Intention for Lazada users in DKI Jakarta. However, Perceived Ease of Use has nonsignificant effect on Repurchase Intention for Lazada users in DKI Jakarta.